ABOUT THE ISSUES OF THE WATER RESOURCES MANAGEMENT AND WATER USE REGULATORY/METHODICAL BASE DEVELOPMENT IN THE RUSSIAN FEDERATION - Mikhail V. Bolgov; Eugeny V. Venitsianov; Sergey N. Shashkov (Водное хозяйство России: проблемы, технологии, управление)
The article considers the main problems of water complex management related to the shortcomings of the existing system of normative and methodological documentsregulating the activities of the sector. There is currently no overall water management system throughout the country. Among the most important problems mentioned is the lack of assessment of the reliability of data on water use and consumption, given in the form of 2TP-water form and other reporting materials supplied by departments as state reports. The system of standards is unsatisfactory. The methods used to calculate the state of water bodies have become obsolete, starting with the assessment of background states, pollution of water bodies from point and diffuse sources. It is noted that the experience accumulated in the industry in the application of regulatory documents requires constant work on the analysis of their effectiveness and improvement, which today is not carried out to a sufficient extent. To coordinate the development of new and editing existing regulatory and methodological documents, it is recommended to create a methodological center under the Ministry of Natural Resources and Ecology with the involvement of leading specialists of the Russian Federation.